The effect of solvent choice on the mechanical properties of carbon nanotube-polymer composites - COLEMAN, JONATHAN; BLAU, WERNER (My University, 2007)
Dispersions of single walled nanotubes in N-methyl-2-pyrrolidone have been exposed to water and variations in storage temperature. The subsequent degradation of dispersion quality has been monitored using sedimentation, UV-vis-NIR, and AFM measurements. Four parameters derived from AFM; the root-mean-square bundle diameter, the total number of dispersed objects (individuals and bundles) per unit volume of dispersion, the number fraction of individual nanotubes, and the number of individual nanotubes per unit volume of dispersion were used to quantitatively characterize the dispersion quality as a function of water content and storage temperature. In addition the positions of the nanotube absorption peaks were used to track dispersion quality, with redshifts taken as an indication of aggregation. It was found that water can rapidly shift the dispersion to a new but more aggregated equilibrium state. In particular the population of individual nanotubes falls to zero for relatively low amounts of added water. The dispersion quality decreases with increasing water content, reaching a plateau for all metrics by 20 vol% added water. In addition, it was also identified that low temperature treatment, i.e. -16, -18, -20, and -22 ?C (all above the freezing point of NMP) does not influence the dispersion quality and stability regardless of the standing time. However, freezing (-80 ?C) or heating (80 ?C ) the dispersion leads to a substantial degradation of the dispersion quality and stability.
PUBLISHED
Keywords: Physics; nanotubes